REFORMULASI HUKUM PIDANA TERKAIT TINDAKAN KEBIRI TERHADAP PELAKU KEKERASAN SEKSUAL - I Gusti Agung Virlan Awanadi; I Ketut Rai Setiabudhi (Jurnal Komunikasi Hukum, 2023)
Sexual violence is an act that harms the values ​​embodied in decency and religious norms. The government issued a policy, a Government Regulation, to address this issue by administering chemical castration to sexual violence perpetrators. The purpose of this study is to reformulate the Government Regulation Implementation in order to find the appropriate reformulation of future regulations against perpetrators of sexual violence. This is because there has been a lot of debate for and against this issue. The methods of normative legal research, which are related to norms and approach statutory regulations and concepts, are used in problem solving. Castration was found to have no justification in this study. influenced by varying opinions and provisions regarding castration. Examples include doctors refusing to execute sexual violence perpetrators and going against the 1945 Constitution in Article 28B regarding the right to continue offspring. The implementation of castration in the Child Protection Stipulation Law itself can be removed to reformulate the castration sanction policy. In the Government Regulation for the Implementation of Castration, sexual violence cases can only be handled by rehabilitation facilities. In addition, the Criminal Code, the Elimination Of Domestic Violence Law, and the Criminal Acts Of Sexual Violence Law all already contain provisions that are more pertinent to handling cases of sexual violence.